“What do you base your students' learning success on?: "A profile analysis of teachers' interpersonal causal attributions - Kling, Ines; Reschke, Katharina; Buhl, Monika (ISSBD 2024, 2024)
Teachers’ interpersonal causal attributions can describe their perceptions concerning the causes underlying student performance. Most research in the context of theoretical assumptions outlined in Weiner’s (1985, 2000) attribution theory has explored teacher attributions with respect to success and failure outcomes, often directly reflecting on particular students (Wang/Hall 2018). In this study, we sought to identify attribution profiles for teacher-perceived causes of their students’ learning success in general. - Secondary school teachers (n=66; 54,8% female) attributed learning success to six factors - student-related (cultural&social background, intelligence, student effort) and school-/teacher-related (school&instructional quality) - and rated them on a cumulated scale from 1 to 100. Further measures included scales on individual reference standard, solicitude and teaching style (α≤.703). Data came from the first measurement occasion of a longitudinal development study on teachers’ awareness for adolescents with migration background (BASF et al. 2023). - Using Latent Profile Analyses, four different attribution profiles were identified: P1 shows high attributions (p<.10) to both school-/teacher-related factors. P2 is relatively balanced. Cultural background is highly attributed to in P3 (p<.10). P4 shows the highest attribution to social background (p<.10) and lowest to student effort (p<.10). Results will illustrate profiles (in relation to teacher-student-interaction). Discussion will focus on the profiles and factor nature, an expansion to Weiner’s traditional factors. Further, its contribution to prior research that suggests that teachers’ attributions impact their instructional behaviors will be discussed.
Gesehen am 21.05.2025